2003
DOI: 10.1074/jbc.m305930200
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Autoactivation of Asparaginyl Endopeptidase in Vitro and in Vivo

Abstract: Mammalian asparaginyl endopeptidase (AEP) or legumain is a recently discovered lysosomal cysteine protease that specifically cleaves after asparagine residues. How this unusually specific lysosomal protease is itself activated is not fully understood. Using purified recombinant pro-enzyme, we show that activation is autocatalytic, requires sequential removal of C-and N-terminal pro-peptides at different pH thresholds, and is bimolecular. Removal of the N-terminal propeptide requires cleavage after aspartic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
147
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 58 publications
15
147
0
Order By: Relevance
“…In addition to the ∼38 kDa predominant active form of legumain, a faint ∼40 kDa protein was labeled by both probes and was also immunodepleted by legumain specific antisera. This protein likely corresponds to the p46 intermediate form of legumain that has been reported to retain enzymatic activity [10]. A ∼50 kDa polypeptide was labeled in the RAW264.7 extracts, presumably corresponding to the ∼56 kDa proenzyme of legumain [10].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In addition to the ∼38 kDa predominant active form of legumain, a faint ∼40 kDa protein was labeled by both probes and was also immunodepleted by legumain specific antisera. This protein likely corresponds to the p46 intermediate form of legumain that has been reported to retain enzymatic activity [10]. A ∼50 kDa polypeptide was labeled in the RAW264.7 extracts, presumably corresponding to the ∼56 kDa proenzyme of legumain [10].…”
Section: Introductionmentioning
confidence: 89%
“…This protein likely corresponds to the p46 intermediate form of legumain that has been reported to retain enzymatic activity [10]. A ∼50 kDa polypeptide was labeled in the RAW264.7 extracts, presumably corresponding to the ∼56 kDa proenzyme of legumain [10]. Previous studies using saturating concentration of ABPs have demonstrated labeling of inactive protease zymogens due to flexibility of pro-peptide binding in the active site [11].…”
mentioning
confidence: 85%
“…Legumain is a lysosomal protease, appears to be expressed in response to stress (66), and may be secreted from cells under some conditions (67), and like cathepsin L it may be active in the pericellular environment (68). Legumain is expressed in various organs (69) and was found in macrophages (70), dendritic cells (71), and in vivo in tumors with high invasive and metastatic potential (66). Under these conditions, legumain may be responsible for processing of CCL15 to the molecule CCL15 and may than support the immune response or the malignant character of a tumor.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the ablation of one activity may impact on others. For example, conversion of pro-AEP involves first autoactivation but then further processing by other enzymes [6]. In turn, AEP is absolutely required for conversion of cathepsins B, L and H from a single chain to the normal two-chain form [7].…”
mentioning
confidence: 99%